2019
DOI: 10.14529/ctcr190301
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Approach to Normalized Difference Vegetation Index Forecast by Artificial Neural Network: Example of Diyala River Basin

Abstract: This study examines the perspective of artificial neural networks for forecast Normalized Differential Vegetation Index (NDVI) on Diyala River basin and also how information about of bioclimatic landscapes will affect to forecasting performance. To do this, in the first stage of the experiment, a total of 20 perceptrons with different one hidden layer architectures were trained with sitespecific variables (latitude, longitude, minimal, maximal and mean height, landcover type) and seasonal meteorological variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Note that the temporal delay in the vegetation response to environmental changes should be considered when looking for the sensitivity of ecosystems to climate variability (Wu et al, 2015). However, in our recent work (Alhumaima & Abdullaev, 2019), found that the maximum biological productivity during the growing season for Diyala river basin, a tributary of Tigris, is controlled by seasonal winter precipitation and January-March mean temperatures. Also showed that the neural network-based prediction of the spatiotemporal NDVI can be improved by using additional zonal landscape input predictor or by constructing an individual predicting model for each one of the zonal landscapes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Note that the temporal delay in the vegetation response to environmental changes should be considered when looking for the sensitivity of ecosystems to climate variability (Wu et al, 2015). However, in our recent work (Alhumaima & Abdullaev, 2019), found that the maximum biological productivity during the growing season for Diyala river basin, a tributary of Tigris, is controlled by seasonal winter precipitation and January-March mean temperatures. Also showed that the neural network-based prediction of the spatiotemporal NDVI can be improved by using additional zonal landscape input predictor or by constructing an individual predicting model for each one of the zonal landscapes.…”
Section: Introductionmentioning
confidence: 91%
“…The maximum value compositing (MVC) method was used to produce monthly NDVI maps and minimize the effects of atmospheric, cloud contamination, and solar zenith angle (Alhumaima & Abdullaev, 2019). Additionally, NDVI pixels less than 0.1 were excluded from the analysis and considered as non-veg-etated (Xu et al, 2016;Alhumaima & Abdullaev, 2019).…”
Section: Ndvi Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the spring seasons of 2000,2006,2008,2009,2011, and 2012 there were virtually no green areas. In fact, during these years, the Tigris and Euphrates basin experienced severe droughts (e.g., Kelley et al 2015;Muhaimeed and Al-Hedny 2013;Mathbout et al 2018;Alhumaima and Abdullaev 2018).…”
Section: ) Visual Analysis Of Ndvimentioning
confidence: 99%